"A Time to Dance": Music, the Bible and the Book of Ecclesiastes. (December 2014) - Dell, Katharine J.
This article explores the burgeoning interest in biblical studies in the use of the Bible in music, as a medium and as an ever fresh way of expounding and expressing the stories and sentiments of the Bible. It looks at some recent scholarship on the Bible and music and then goes on to look closely at a sample book, that of Ecclesiastes, to see which texts have been used as inspiration for musical expression and in what ways that has evolved in ever fresh historical and cultural contexts. It is seen that particular themes such as time (Eccl 3:1-8), the fate of humans and animals (Eccl 3:9-14) and that of 'vanity' (the repeated refrain of the book) have been of particular interest to librettists and composers.